PENGARUH KREDIBILITAS KONTEN EDUKASI KANAL YOUTUBE KOK BISA? TERHADAP KEBUTUHAN INFORMASI FOLLOWERS - Siti Nur Aisyah; Rorong, Michael Jibrael (LPPM Universitas Putera Batam, 2023)
The modern human being can be said to be very reliant on the ease and convenience of the internet. In the middle of the 2000s, the Internet had a boom that transformed it into a platform for disseminating content. As a result, numerous blogs, video sharing websites, and social networking sites appeared that year. Additionally, social media can be used for the good of individuals, communities, businesses, and organizations. Youtube is one form of social media that is popular with people, groups, businesses, and organizations. Credibility is the perception of a communicator based on his point of view, which offers an evaluation of the personality or character of a communicator. For a communicator, credibility is a quality they need to possess since it allows them to transmit facts and thoughts with confidence. The purpose of this study is to ascertain the trustworthiness of educational information on YouTube and its impact. Why is that? to the followers' informational requirements. A Likert scale is used to collect data through online surveys or questionnaires as part of the quantitative research methodology. According to the study's findings, followers of a YouTube account may be more interested in receiving information if it is credible. Why is that? How come, in the eyes of a YouTube account's followers? The information displayed is a subjective evaluation of the procedure or system employed by the YouTube account holder. Why is that? How come, in the eyes of a YouTube account's followers? The information displayed is a subjective evaluation of the procedure or system employed by the YouTube account holder. Why is that? in producing valuable material that meets the community's overall information demands. The conclusion is that the reliability of the content (X1) on the Youtube account has a favorable affect on raising interest in the need for information (Y). How come? with a percentage of 29,8%.Keywords: Credibility, Youtube Account Information Needs